Visual histories of Austria - Bischof, Günter, 1953- (New Orleans, LA : University of New Orleans Press, 2021)
"Visual histories in 19th and 20th century Austria are documented here, from court photography and nature photography to political photography. A single photo studio will be analyzed documenting lives in Western Austria as well as a photo archive and its special collections regarding mountains. Imperial Austria is present in the pictures of court photographer Ludwig Angerer. Photos of wars figure heavily in this volume, from the brutal fighting in the Dolomites during WWI to National Socialism, concentration camps and the air war during WW II. Postwar life and the American presence in Austria will be documented from the end of the war to the postwar occupation--seen through the lenses of U.S. star photographer Yoichi Okamoto. Cartoons will be analyzed and the role of exhibits in modern public diplomacy"--
I. Introduction. The interreg-project "Lichtbild/Argento Vivo" and its results to promote the importance of historic photography -- The Hiller photo studio in Bezau, Vorarlberg, and the advance of photography on social life in rural Austria -- II. Austrian Empire & World War I. Ludwig Angerer (1827-1879), court photographer -- Draw to live : Jewish cartoonists in Central Europe 1900-1945 -- In/visibility of violence : the First Worl War in Austrian private photo albums -- III. World War II. Depicting "Austria's" air war 1914-1945 : an analysis of the creation and reinterpretation of the Austrian aviation archives and the Viennese exhibition "Der Luftterror" -- The visual memory of Mauthausen -- Visualizing "Zero Hour" 1945 : end of war vs. liberation in Austrian visual memory, 1945-2005 -- IV. Postwar. Yoichi Okamoto's eye on Austria in postwar Europe -- Beyond the edelweiss : Austrian image in the United States -- Mountain pictures : a special look into the collections of the Tyrolean Photo Archive (TAP) -- V. Book reviews. Alison Frank Johnson : Rudolf Agstner, Handbuch des k.k./k.u.k. Konsulardienstes : Die Konsulate der Donaumonarchie vom 18. Jh. bis 1918 (Vienna, new academic press, 2018) -- Gary B. Cohen : Andreas Weigl, Von der Existenzsicherung zur Wohlstandsgellschaft : Überlebensbedingungen und Lebenschancen in Wien und Niederösterreich von der Mitte des 19. Jahrhunderts bis zur Gegenwart (Vienna : Böhlau, 2020) -- Oswald Überegger : Bernhard Bachinger, Die Mittelmächte an der Saloniki-Front 1915-1918 : Zwischen Zweck, Zwang und Zwist (Paderborn : Schöningh, 2019) -- Ingrid Böhler : Stefan Karner and Peter Ruggenthaler, eds., 1938 : Der "Anschluss" im internationalen Kontext (Graz : Leykam, 2020) -- Evan B. Bukey : Dieter J. Hecht, Michaela Raggam-Blesch, and Heidemarie Uhl, eds., Letzte Orte : die Wiener Sammellager und die Deportationen 1941/42 (Vienna : Mandelbaum Verlag, 2019) -- Anton Pelinka : Margit Reiter, Die Ehemaligen : der Nationalsozialismus und die Anfänge der FPÖ (Göttingen : Wallstein, 2019) -- Laura Morowitz : Gundolf Graml, Revisiting Austria : tourism, space and national identity, 1945 to the present (New York : Berghahn Books, 2020) -- Günter Bischof : Manfred Mugrauer, Die Politik der KPÖ 1945-1955 : von der Regierungsbank in die innenpolitische Isolation (Göttingen : V&R unipress/Vienna University Press, 2020) -- Stafan Maurer : Joshua Parker, ed., Blossoms in snow : Austrian refugee poets in Manhattan (New Orleans : University of New Orleans Press, 2020) -- Peter Berger : Jens Malte Fischer, Karl Kraus : der Widersprecher (Vienna : Zsolnay, 2020) -- Tim Kirk : Kurt Bauer, Der februaraufstand 1934 : Fakten und Mythen (Vienna : Böhlau, 2019) -- Tim Corbett : Jack Bray, Alone against Hitler : Kurt von Schuschnigg's fight to save Austria from the Nazis (Guilford : Prometheus, 2020) -- Michael Burri : Stefan Maurer, Wolfgang Kraus und der österreichische Literaturbetrieb nach 1945 (Vienna : Böhlau, 2020).
"This volume was conceived out of a panel in the 2019 German Studies Association meeting Portland, Oregon (Kofler/Siller, Markova, and Richter papers)."--Introduction
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Photography in historiography; Museums and photography -- Austria; Austria -- Historiography; Photography -- Austria -- History -- 20th century; Photographers -- Austria -- History -- 20th century; Archives -- Austria; Pictures as information resources -- Austria; Photographie en historiographie; Musées et photographie -- Autriche; Photographie -- Autriche -- Histoire -- 20e siècle.; Photographes -- Autriche -- Histoire -- 20e siècle.; Archives -- Autriche; Illustrations, images, etc. (Sources d'information) -- Autriche; HISTORY -- Europe -- Austria & Hungary; Archives; Historiography; Museums and photography; Photographers; Photography; Photography in historiography; Pictures as information resources; Austria; 1900-1999; History